The Impact of Correctional CCTV Cameras on Infractions and Investigations: A Synthetic Control Approach to Evaluating Surveillance System Upgrades in a Minnesota Prison - Lawrence, Daniel S. (Criminal justice policy review, 2022)
Internal surveillance systems have long been used by prisons to combat misbehavior. Yet, limited research has focused on cameras’ preventive potential, failing to examine their utility in investigations. Using comparative interrupted time-series analyses and synthetic control methods, this study evaluates the impact of upgrading a surveillance system in a prison’s housing unit on total infractions and infractions resulting in guilty dispositions. Upgrades were two-phased, allowing us to examine the differential effects of replacing outdated cameras versus installing new cameras. One comparison unit came from the same facility as the treatment unit, while the other was synthetically generated from units in other prisons. We found limited evidence that the interventions reduced infractions, though there was a stronger link between the interventions and an increase in guilty dispositions, particularly from the installation of new cameras to reduce blind spots. We discuss the implications of these findings for policy and research.